Framing analyses of Malaysia’s media outlets and editorial decisions concerning frame preferences after the 2008 general election - Baharin, Muhd Izawan; Waheed, Moniza; Ahmad Ghazali, Akmar Hayati; Zamri Ahmad, Abd Mua'ti (Universiti Putra Malaysia Press, 2020)
A study was conducted to investigate the journalistic practices in Malaysian news outlets post-2008 general elections through a combination of content analysis and interviews. Through a content analysis of news articles of an UMNO-owned media (Utusan Malaysia) as well as an independent news portal (Malaysiakini), the study identified five different news frames (conflict, human interest, economic consequences, morality, and responsibility) employed in the news articles. The study established that the previously government owned media relied heavily on the morality frame, while the responsibility frame was most dominant in independent news portals. The study revealed that the responsibility frame was written in a positive tone while morality and conflict frames were written in negative tones. The study suggests that there were differences and similarities in terms of framing practices employed by the media. It also found that the tonality of the news strengthened the functions of frames. To further understand the relationship between the frames and journalistic practices, semi-structured interviews with editors from both media outlets were conducted. The editors noted that their organizations’ agendas functioned as guidelines on how political issues were highlighted. The interviews also revealed that although both news outlets received political instructions, the media still strived to promote fair reporting within their scope and capacity.